TRENDS IN THE DEVELOPMENT OF EXTREME TOURISM IN UKRAINE - PANKIV, Natalia; DROZD, Nazar (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the essence of the concept of “extreme tourism”, as well as examines in detail its current state and prospects for development in Ukraine and the world. The general characteristic of the tourist potential of extreme tourism in Ukraine is given and its main centers are analyzed. A SWOT analysis, research of shortcomings and possible ways to improve extreme recreation, and outlined trends in the development of extreme tourism in Ukraine. It is established that the most popular region for this type of tourism in Ukraine is the Carpathians, it combines well-developed infrastructure and natural environment, but does not use its full potential. In general, Ukraine has a large number of natural and man-made sites for the development of this type of tourism. Creating a competitive tourism product that can meet the tourism needs of the population and ensure the development of territories - is a key task of its development.It is emphasized that in times of crisis caused by the long-lasting Coronavirus pandemic and the full-scale invasion of the Russian Federation, when the psychological burden is very high and the amount of money available for recreation and entertainment is limited, it is necessary to develop local extreme tourism. and can stimulate sectors of the economy that are compatible with tourism. Therefore, for the development of extreme tourism, the main directions of public policy should be: conservation of tourist resources; improving the regulatory framework; creation of economic conditions to stimulate tourism development; investment attraction; ensuring the safety of tourists. Solving these problems will increase the economic and social level of development of the country as a whole.
Keywords: extreme tourism; types of extreme tourism; tourist potential; Ukraine